The Effect Of Democratic Leadership And Work Environment On Employee Performance Through Job Performance - Deni Hadiatullah; Budi Santoso; Riyanto Setiawan Suharsono; Nursaid Nursaid (UNIVED Press, 2026)
This study aims to analyze the influence of democratic leadership and the work environment on employee performance in Kaliwates District, as well as the role of job performance as an intervening variable. The study used a quantitative approach, using a survey method and distributing questionnaires to employees in Kaliwates District. Data analysis was conducted using inferential statistical techniques to test the direct and indirect relationships between variables. The results indicate that democratic leadership and the work environment have a positive and significant effect on employee performance. Furthermore, job performance acts as an intervening variable, strengthening the influence of both factors on improving employee performance. These findings highlight the importance of implementing a participatory leadership style and managing a conducive work environment to encourage work performance, thus optimally improving employee performance. This study recommends improving the quality of leadership and work environment management, along with efforts to develop employee performance, to achieve excellent public service in Kaliwates District.